Methylation-specific multiplex ligation-dependent probe amplification analysis of subjects with chromosome 15 abnormalities - Bittel, Douglas C; Kibiryeva, Nataliya; Butler, Merlin G (Genetic testing, 2007)
Prader-Willi syndrome (PWS) and Angelman syndrome (AS) are neurodevelopmental disorders caused by loss of expression of imprinted genes from the 15q11-q13 region. They arise from similar defects in the region but differ in parent of origin. There are two recognized typical 15q11-q13 deletions depending on size and several diagnostic assays are available but each has limitations. We evaluated the usefulness of a methylation-specific multiplex ligation-dependent probe amplification (MLPA) kit consisting of 43 probes to detect copy number changes and methylation status in the region. We used the MLPA kit to genotype 82 subjects with chromosome 15 abnormalities (62 PWS, 10 AS and 10 individuals with other chromosome 15 abnormalities) and 13 with normal cytogenetic findings. We developed an algorithm for MLPA probe analysis which correctly identified methylation abnormalities associated with PWS and AS and accurately determined copy number in previously assigned genetic subtypes including microdeletions of the imprinting center. Furthermore, MLPA analysis identified copy number changes in those with distal 15q deletions and ring 15s. MLPA is a relatively simple, cost-effective technique found to be useful and accurate for methylation status, copy number and analysis of genetic subtype in PWS and AS, as well as other chromosome 15 abnormalities.